2017
DOI: 10.1002/cctc.201700018
|View full text |Cite
|
Sign up to set email alerts
|

Dual Gold(I)‐catalyzed Cyclization of Dialkynyl Pyridinium Salts

Abstract: Novel dialkynyl pyridines were synthesized and protected as alkyl salts for dual gold(I)‐catalyzed cycloisomerization. Different alkyl groups and counter ions were screened for the salts, with benzyl and hexafluorophosphate providing the best results. The cyclization led to NMR yields of >95 % being obtained for a number of substrates. Step‐wise hydrogenation of products could be performed in one‐pot by Pd/C, with selective reduction of the double bonds, followed by deprotection of the benzyl group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 88 publications
0
7
0
Order By: Relevance
“…(2)). [286] The diyne cyclization by dual catalysis has focused so far on the CÀ H insertion of substituents at the alkyne terminus. However, a report by Ohno, Fujii and Hashmi described the CÀ H insertion of gold vinylidenes 350 through substituents in the tether of 351 via σ,π-propyne gold acetylide catalysis, leading to the synthesis of an array of polycyclic fused products (Scheme 63).…”
Section: Hydroarylation Of Enyne and Diyne Surrogatesmentioning
confidence: 99%
See 1 more Smart Citation
“…(2)). [286] The diyne cyclization by dual catalysis has focused so far on the CÀ H insertion of substituents at the alkyne terminus. However, a report by Ohno, Fujii and Hashmi described the CÀ H insertion of gold vinylidenes 350 through substituents in the tether of 351 via σ,π-propyne gold acetylide catalysis, leading to the synthesis of an array of polycyclic fused products (Scheme 63).…”
Section: Hydroarylation Of Enyne and Diyne Surrogatesmentioning
confidence: 99%
“…Likewise, a series of dialkynyl pyridinium salts 348 under dual activation catalysis by [IPrAu(I)] + species reacted via a cascade sequence of 5‐ endo cyclization/Csp 3 −H activation to generate dihydropentalenopyridinium salts 349 (Scheme 62, Eq. (2)) [286] …”
Section: Hydroarylation Of Enyne and Diyne Surrogatesmentioning
confidence: 99%
“…352 In addition to o-dialkynylbenzenes, 1,2-bisethynyl-pyridine and -thiophene were shown to be viable substrates. 353,354 The cyclization under dual-gold catalysis can also be practiced with diynes containing a nonarene tether. Diyne 731, prepared by Ugi four-component coupling, undergoes double cyclization under gold catalysis to provide bicyclic pyridone 732 (Scheme 148).…”
Section: Hydrogen Transfermentioning
confidence: 99%
“…For example, and by analogy with the work performed with aryldiyne substrates, the group of Hashmi developed a procedure for the synthesis of polyclic fused pyridines 80 from pyridinium substrates 77 (Scheme 20). 34 Initial tests showed that the cycloisomerization could not be directly performed from the 'free' pyridines, presumably due to their capacity to strongly bind to gold catalysts. It is also interesting to note that while simple methylpyridium salts exhibit a low to moderate reactivity, the benzyl ones 77 bearing either a…”
Section: Scheme 19mentioning
confidence: 99%